Average rate (student - teacher) in Saudi Arabia in the light of international comparisons - Al Ghamdi, Saeed bin Mohammed Al Aatiq; Abdeen, Mahmoud Abbas (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed to make comparisons in the student/teacher rate with some developed countries and global rates by reviewing the global average and the average of Arab countries and the target within the development plan in the index (student/teacher), and to identify the reality of the student/teacher rate in Saudi Arabia through Official statistics, identify the level of achieving a student/teacher rate between the different educational areas in The Kingdom of Saudi Arabia and determine the actual rate in the three primary, middle and secondary levels of both sexes, and identify the level of achieving the student/teacher index rate in Saudi Arabia in light of the classification of schools according to student numbers. The researcher used the office approach. The most important results of the study were: The consensus of the target in the development plan with the global average student/teacher rate index of 25 students per teacher, there is a disparity in the index rates between the selected countries and ranging from one teacher for every 11 students to 23 students, that the actual student/teacher index is far from the target in the development plan. 9th and far from the global average, there is a disparity in the rates of the index in the Kingdom between the main educational areas and ranging from 6.9 in the courtyard to 12.9 in Tabuk, and this can be assumed that the indicator decline in low-density areas with the availability of schools at full capacity, that 45.2% of boys' schools and 38.7% Girls' schools do not exceed 100 students.
Keywords: indicator; student teacher rate; international comparisons